Sarcandra glabra Extract Reduces the Susceptibility and Severity of Influenza in Restraint-Stressed Mice. (1st November 2012) - Cao, Hui-Juan; Tan, Rui-Rong; He, Rong-Rong; Tang, Lu-Ping; Wang, Xin-Luan; Yao, Nan; Duan, Wen-Jun; Hu, Yuan-Ao; Yao, Xin-Sheng; Kurihara, Hiroshi
Abstract : Sarcandra glabra, as a type of "antipyretic-detoxicate drugs", has always been widely used in traditional Chinese medicine (TCM). The Sarcandra glabra extract (SGE) is applied frequently as anti-inflammatory and anti-infectious drug in folk medicine. However, relative experiment data supporting this effective clinical consequence was limited. In order to mimic the physiological conditions of the susceptible population, we employed restraint stress mouse model to investigate the effect of SGE against influenza. Mice were infected with influenza virus three days after restraint, while SGE was orally administrated for 10 consecutive days. Body weight, morbidity, and mortality were recorded daily. Histopathologic changes, susceptibility genes expressions and inflammatory markers in lungs were determined. Our results showed that restraint stress significantly increased susceptibility and severity of influenza virus. However, oral administration of SGE could reduce morbidity, mortality and significantly prolonged survival time. The results further showed that SGE had a crucial effect on improving susceptibility markers levels to recover the balance of host defense system and inhibiting inflammatory cytokines levels through down-regulation of NF-κ B protein expression to ameliorate the lung injury. These data showed that SGE reduced the susceptibility and severity of influenza.